Differences of the Lithuanian Regions Situation in the Labour Market - Pocius, Arūnas; Burneika, Donatas (Lithuanian Journal of Statistics, 2017)
The article is based on the results of National science program ‘Welfare society’ project ‘Regional disparities of welfare inLithuania’ (project number GER-005/2017). The project is funded by the Lithuanian Council of Science. The aim of the work is toestimate features of index distribution of labor market and labor resources (working-age people) in the main country regions.Considering the fact about migration changes, a lot of attention in the paper is paid to the estimation of demographic situation impacton the labour market. Apart from the ordinary statistical data, we use results of systemic poverty problem analysis in Lithuania.According to the disposition of information and its opportunities comparison, the data of counties and municipalities were usedduring the research. Different levels of information have helped to detect more detailed differences between labour markets in theregions. The comparison of different sources of information has revealed peculiarities of unemployment change and differentiationthat have not been explored as yet.
Keywords: unemployment rate; population activity; problematic regions; demographic changes; labour market; group of regions; migration; employment rate